The Role of Echocardiography in the Contemporary Diagnosis and Prognosis of Cardiac Sarcoidosis: A Comprehensive Review - Joseph Okafor; Rajdeep Khattar; Rakesh Sharma; Vasilis Kouranos (Life, 2023)
Cardiac sarcoidosis (CS) is a rare inflammatory disorder characterised by the presence of non-caseating granulomas within the myocardium. Contemporary studies have revealed that 25–30% of patients with systemic sarcoidosis have cardiac involvement, with detection rates increasing in the era of advanced cardiac imaging. The use of late gadolinium enhancement cardiac magnetic resonance and 18fluorodeoxy glucose positron emission tomography (FDG-PET) imaging has superseded endomyocardial biopsy for the diagnosis of CS. Echocardiography has historically been used as a screening tool with abnormalities triggering the need for advanced imaging, and as a tool to assess cardiac function. Regional wall thinning or aneurysm formation in a noncoronary distribution may indicate granuloma infiltration. Thinning of the basal septum in the setting of extracardiac sarcoidosis carries a high specificity for cardiac involvement. Abnormal myocardial echotexture and eccentric hypertrophy may be suggestive of active myocardial inflammation. The presence of right-ventricular involvement as indicated by free-wall aneurysms can mimic arrhythmogenic right-ventricular cardiomyopathy. More recently, the use of myocardial strain has increased the sensitivity of echocardiography in diagnosing cardiac involvement. Echocardiography is limited in prognostication, with impaired left-ventricular (LV) ejection fraction and LV dilatation being the only established independent predictors of mortality. More research is required to explore how advanced echocardiographic technologies can increase both the diagnostic sensitivity and prognostic ability of this modality in CS.